The heat of the battle: inflammation’s role in prostate cancer development and inflammation-targeted therapies - Ujjawal Sharma; Anidrisha Sahu; Himanshu Shekhar; Bunty Sharma; Shafiul Haque; Damandeep Kaur; Hardeep Singh Tuli; Astha Mishra; Faraz Ahmad (Discover Oncology)
Abstract In prostate cancer (PC), chronic inflammation silently guides disease progression, playing a significant role. As a major global health concern, PC contributes to high mortality rates and rising new cases worldwide, highlighting the urgent need for research into the molecular mechanisms behind this disease. Notably, the persistence of inflammation actively promotes cancer development, including in PC. This review explores the complex relationship between inflammation and PC, examining the molecular pathways, genetic and environmental factors, and clinical implications involved in inflammation-driven carcinogenesis. From cellular and molecular elements of the inflammatory microenvironment to mechanisms like epithelial-to-mesenchymal transition (EMT), reactive oxygen species (ROS) generation, and inflammasome activation, these processes highlight inflammation’s influence on PC progression and metastasis. Furthermore, this review discusses current therapeutic strategies targeting inflammation in PC management and identifies future research directions aimed at unraveling the complexities of inflammation-induced PC (Supplementary Fig. 1). It defines the complex relationship between inflammation and PC, emphasizes the importance of targeting inflammation therapeutically and highlights innovative approaches in PC treatment. Graphical Abstract